Association of lung ultrasound score with 72-hour intubation needs in pneumonia patients presenting to the emergency department - Tanyaporn Nakornchai; Apichaya Monsomboon; Panrada Pathomkajonkul; Ronnapop Jaluspikultip; Rathachai Kaewlai; Nattakarn Praphruetkit; Tipa Chakorn; Sattha Riyapan; Usapan Surabenjawong; Wansiri Chaisirin; Netiporn Thirawattanasoot (BMC Emergency Medicine)
Abstract Background The lung ultrasound (LUS) score is a semi-quantitative tool used to predict clinical outcomes in conditions such as congestive heart failure and acute respiratory distress syndrome. However, its role in pneumonia remains unclear. This study aimed to determine whether the LUS score is associated with the need for intubation within 72 h of emergency department (ED) presentation. Methods This prospective observational study enrolled adults (≥ 18 years) who were diagnosed with pneumonia in the ED. The LUS score was calculated by summing findings from 12 thoracic regions. We then examined the relationship between the total LUS score and the need for endotracheal intubation (ETI). Results Forty-five patients were included. The median LUS score was 13.0 (IQR: 5.5‒19.0). Patients who required ETI had a significantly higher median LUS score (19.0, IQR: 17.0‒26.0) compared with those who did not require ETI (12.0, IQR: 4.25‒18.0; P = 0.002). The LUS score demonstrated strong predictive ability for ETI, with an area under the receiver operating characteristic curve of 0.83 (95% CI: 0.71‒0.95). The optimal cutoff value of 16 yielded a sensitivity of 88.9%, specificity of 69.4%, positive predictive value of 42.1%, and negative predictive value of 96.2%. Higher LUS scores were significantly associated with increased 28-day mortality (P = 0.04). Conclusions Among patients with pneumonia presenting to the ED, the LUS score was associated with the need for ETI and was linked to higher 28-day mortality. Trial registration This study was registered in Thai clinical trial registry (TCTR20230518003) on May 18, 2023.